Missed opportunities for NCD multimorbidity prevention in adolescents and youth living with HIV in urban South Africa - Monika Kamkuemah; Blessings Gausi; Tolu Oni (BMC, 2020)
Abstract Background Epidemiological transition in high HIV-burden settings is resulting in a rise in HIV/NCD multimorbidity. The majority of NCD risk behaviours start during adolescence, making this an important target group for NCD prevention and multimorbidity prevention in adolescents with a chronic condition such as HIV. However, there is data paucity on NCD risk and prevention in adolescents with HIV in high HIV-burden settings. The aim of this study was to investigate the extent to which NCD comorbidity (prevention, diagnosis, and management) is incorporated within existing adolescent HIV primary healthcare services in Cape Town, South Africa. Methods We reviewed medical records of 491 adolescents and youth living with HIV (AYLHIV) aged 10-24 years across nine primary care facilities in Cape Town from November 2018-March 2019. Folders were systematically sampled from a master list of all AYLHIV per facility and information on HIV management and care, NCDs, NCD risk and NCD-related health promotion extracted. Results The median age was 20 years (IQR: 14-23); median age at ART initiation 18 years (IQR: 6-21) and median duration on ART 3 years (IQR: 1.1-8.9). Fifty five percent of participants had a documented comorbidity, of which 11% had an NCD diagnosis with chronic respiratory diseases (60%) and mental disorders (37%) most common. Of those with documented anthropometrics (62%), 48% were overweight or obese. Fifty nine percent of participants had a documented blood pressure, of which 27% were abnormal. Twenty-six percent had a documented health promoting intervention, 42% of which were NCD-related; ranging from alcohol or substance abuse (13%); smoking (9%); healthy weight or diet (9%) and mental health counselling (10%). Conclusions Our study demonstrates limited NCD screening and health promotion in AYLHIV accessing healthcare services. Where documented, our data demonstrates existing NCD comorbidity and NCD risk factors highlighting a missed opportunity for multimorbidity prevention through NCD screening and health promotion. Addressing this missed opportunity requires an integrated health system and intersectoral action on upstream NCD determinants to turn the tide on the rising NCD and multimorbidity epidemic.